A new species of Axinaea (Melastomatacee: Merianieae) from North of Peru - Sagástegui Alva, Abundio (2010)
Axinaea wurdackii Sagást., S. J. Arroyo & E. Rodr. sp.nov. is described and illustrated as a new species of Axi- naea Ruiz & Pav. (Melastomataceae: Merianieae) from Northern Peru (Departments of Cajamarca, La Libertad and Piura). This species is typical of the montane forests and apparently endemic to this part of the country. It is compared with its closest relatives. Additionally data on its geographical distribution, ecology, uses and state of conservation are provided.